Furan‐Extended Helical Rylenes with Fjord Edge Topology and Tunable Optoelectronic Properties. (22nd December 2022) - Luo, Teng; Wang, Yanpei; Hao, Jiahang; Chen, Ping‐An; Hu, Yuanyuan; Chen, Bo; Zhang, Jun; Yang, Kun; Zeng, Zebing
Abstract: Lateral furan‐expansion of polycyclic aromatics, which enables multiple O ‐doping and peripheral edge evolution of rylenes, is developed for the first time. Tetrafuranylperylene TPF‐4CN and octafuranylquaterrylene OFQ‐8CN were prepared as model compounds bearing unique fjord edge topology and helical conformations. Compared to TPF‐4CN, the higher congener OFQ‐8CN displays a largely red‐shifted (≈333 nm) and intensified absorption band ( λ max =829 nm) as well as a narrowed electrochemical band gap (≈1.08 eV) due to its pronounced π‐delocalization and emerging of open‐shell diradicaloid upon the increase of fjord edge length. Moreover, strong circular dichroism signals in a broad range until 900 nm are observed for open‐shell chiral OFQ‐8CN, owing to the excellent conformational stability of its central bis(tetraoxa[5]helicene) fragments. Our studies provide insights into the relationships between edge topologies and (chir)optoelectronic properties for this novel type of O ‐doped PAHs. Abstract : A concise synthetic strategy is reported for preparing lateral furan‐extended rylenes bearing multifold O ‐doping and fjord edge topology. The resultant rylenes display fjord edge length dependent electronic structures and properties. The higher congener witnesses an open‐shell structure and remarkable optoelectronic characteristics such as red‐shifting and NIR‐absorbing capacities, as well as pronounced mirror‐image circular dichroism of chiral diradicaloids.